Scale Effects on the Reduction of Drainage Water and Nitrogen and Phosphorus Loads in Hilly Irrigation Areas - Niannian Yuan; Yalong Li; Yujiang Xiong; Baokun Xu; Fengli Liu; Haolong Fu (Agronomy, 2023)
The objectives of this study were to clarify the effects of scale on farmland drainage water and the nitrogen and phosphorusload discharged in hilly irrigation areas. An experimental study was conducted to monitor the drainage water volume and nitrogen and phosphorus concentrations at the field, lateral ditch (with a control area of 1.16 km2), branch ditch (with a control area of 7.76 km2), and watershed (with a control area of 43.3 km2) scales in the Yangshudang watershed of the Zhanghe Irrigation District during the rice growth period in 2022. The results showed that from the field scale to the watershed scale, the volume of drainage water, total nitrogen load, nitrate nitrogen load, ammonia nitrogen load, and total phosphorus load per unit area were reduced by 74.6%, 88%, 85%, 87%, and 60%, respectively. The loads of total nitrogen, nitrate nitrogen, ammonia nitrogen, and total phosphorus decreased with the increase of scale, showing a pronounced scale effect; however, the infrequent recharge of ponds and weirs and the insufficient storage capacity of ditches led to an increase in nitrogen and phosphorus concentrations and hence an increase in the load discharge instead, as in the branch ditch scale of this study. The scale effect was mainly caused by the reuse of farmland drainage water; thus, the ability of ponds and weirs, ditches, and reservoirs in hilly irrigation areas to regulate nitrogen and phosphorus concentrations should be improved. Irrigation methods have a significant influence on nitrogen and phosphorus load discharge. The control of farmland non-point sources in hilly irrigation areas should focus on controlling drainage water at the late tillering stage and improving the recharge function of ponds and weirs and the storage capacity of ditches above the branch ditch scale so as to control the concentrations of nitrogen and phosphorus pollutants.